Eimeria SPECIES COMPOSITION AND FACTORS INFLUENCING OOCYST SHEDDING IN DAIRY FARM, BANDUNG, INDONESIA - Isrok Malikus Sufi; Umi Cahyaningsih; Etih Sudarnika (BIOTROPIA, 2017)
Coccidiosis is one of the most widespread parasitic diseases affecting cattle worldwide, caused by Eimeria spp. This study aimed to determine the composition of Eimeria species and the factors influencing Eimeria oocyst shedding in dairy farms. A cross-sectional study was conducted in dairy farms in South Bandung District from July 2014 to January 2015. Fecal samples were collected from 400 dairy cattle, consisting of 196 calves aged < 6 months, 37 cattle aged 6–12 months, and 167 cattle aged > 12 months. Samples were examined and quantified for Eimeria species composition and oocyst per gram (OPG) counts using the McMaster technique. A questionnaire was administered to dairy farmers to gather information on cattle health status and husbandry practices. The effects of sex, age, and pen flooring type on OPG values were analyzed using Mann–Whitney and Kruskal–Wallis tests, followed by Dunn’s multiple comparison test. Ten Eimeria species were identified in the infected cattle. Among them, Eimeria bovis showed the highest prevalence (42.5%), followed by Eimeria wyomingensis (39.1%), Eimeria bukidnonensis (32.4%), Eimeria pellita (26.3%), Eimeria auburnensis (19.6%), Eimeria zuernii (17.3%), Eimeria cylindrica (3.9%), Eimeria canadensis (3.9%), Eimeria brasiliensis (3.4%), and Eimeria alabamensis (1.1%). Oocyst shedding was significantly correlated (p < 0.05) with cattle sex, age, and pen flooring type, all of which influenced infection pressure. Younger calves aged < 6 months shed the highest numbers of Eimeria oocysts compared to older cattle. Several factors may contribute to the increased OPG in fecal samples; therefore, maintaining proper sanitation and implementing effective Eimeria control measures are essential for dairy cattle management in KPBS Pangalengan.